2000
DOI: 10.1271/bbb.64.2625
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Amines inDrosophila virilisunder Stress Conditions

Abstract: The effect of heat stress (38 degrees C) on the content of DL-beta-(3,4-dihydroxyphenyl)alanine (DOPA), dopamine, tyramine, octopamine, and their precursor Tyr was studied in adults of two lines of Drosophila virilis contrasting in their stress response. In individuals of line 101 responding to stress by a hormonal stress reaction, the contents of DOPA, dopamine, octopamine, and Tyr were lower than those of line 147 that did not respond to the stress. However, heat stress caused an increase in the contents of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
5

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 30 publications
3
54
0
5
Order By: Relevance
“…Octopamine is often loosely characterised as a 'stress hormone' (Davenport and Evans, 1984a;Birmingham and Tauck, 2003), and levels have been shown to increase in the haemolymph by up to eightfold in response to conditions such as food deprivation (Davenport and Evans, 1984b) or heat stress (Hirashima et al, 2000). Indeed, the widespread changes in brain chemicals we report here, whilst clearly correlated with both solitarization and gregarization, do not necessarily have a causative role.…”
Section: Rapid Changes On Crowding or Isolationmentioning
confidence: 54%
“…Octopamine is often loosely characterised as a 'stress hormone' (Davenport and Evans, 1984a;Birmingham and Tauck, 2003), and levels have been shown to increase in the haemolymph by up to eightfold in response to conditions such as food deprivation (Davenport and Evans, 1984b) or heat stress (Hirashima et al, 2000). Indeed, the widespread changes in brain chemicals we report here, whilst clearly correlated with both solitarization and gregarization, do not necessarily have a causative role.…”
Section: Rapid Changes On Crowding or Isolationmentioning
confidence: 54%
“…The increase in DA content is followed by a sharp decrease in the activity of the key enzyme of its synthesis, tyrosine hydroxylase (TH), and this decrease continues for up to 60 min after the onset of stress exposure (Rauschenbach et al, 1995b). A similar pattern is observed with the OA system, the only difference being that the decrease in activity of tyrosine decarboxylase, the first enzyme involved in OA synthesis, continues for up to 240 min of the stress exposure Hirashima et al, 2000b). The activity of alkaline phosphatase [ALP, the enzyme that regulates the pool of the DA and OA precursor tyrosine (Wright, 1987)] also decreases abruptly under stress conditions (Sukhanova et al, 1996).…”
Section: Introductionmentioning
confidence: 78%
“…In these species, DA content increases sharply as early as 15 min after the beginning of stress exposure (38°C) (Rauschenbach et al, 1993;Hirashima et al, 2000b;Gruntenko et al, 2004). The increase in DA content is followed by a sharp decrease in the activity of the key enzyme of its synthesis, tyrosine hydroxylase (TH), and this decrease continues for up to 60 min after the onset of stress exposure (Rauschenbach et al, 1995b).…”
Section: Introductionmentioning
confidence: 99%
“…Tyrosine acts as a precursor of several stress hormones in insects, including dopamine, octopamine, and tyramine (19,37). In the present study, we found that tyrosine was markedly elevated in the S flies, whereas the levels were intermediate in the H flies and close to control in the HS flies.…”
Section: Fig 4 Dendrograms (A-c) and Pls-da Plots (D-f) Showing Simmentioning
confidence: 99%